Anisotropic Terahertz Microscopy of Lysozyme in Different CrystalLattice Systems - McKinney, J. A.; George, D. K.; Deng, Y.; Markelz, A. G. (Biophysical Journal, 2021)
Long-range vibrational modes of proteins at terahertz (THz) frequencies havebeen associated with protein function and allosteric control. The characteriza-tion of these motions has been challenging due to energy overlap with waterabsorption and a large vibrational density of states. Recently it has been demon-strated both experimentally and theoretically that vibrational bands can be iso-lated using stationary sample anisotropic terahertz microscopy (SSTAM) fororiented samples, typically realized using protein crystals [1, 2]. In those earlymeasurements, inhibitor binding contrast was demonstrated for high symmetrytetragonal crystals. While high symmetry crystals are ideal for structural deter-minations, they can limit the types of vibrations observable in the ATM mea-surements. Here we show a survey of ATM measurements of triclinic,monoclinic and tetragonal crystals, demonstrating the unique signaturesobservable for the different symmetry groups, leading to a more completedetermination of the vibrational hot spots that may contribute to enzymatic ef-ficiency. The SSATM spectra indicate the presence of conserved vibrationalmodes near 40 cm-1 and 55 cm-1 for CEWL in triclinic, monoclinic and tetrag-onal lattice systems respectively. For CEWL in the monoclinic lattice system, aprominent band at 20cm1was consistently observed in the SSATM spectrabut not in the triclinic or tetragonal systems. The conserved bands may repre-sent vibrational modes that are unperturbed by crystal contact forces while thedifferences may be related to unique molecular orientation in different crystalsystems. 1.Niessen, K., Y. Deng, and A.G. Markelz,Near-field THz micropo-larimetry.Opt Express, 2019.27(20): p. 28036-28047. 2.Romo, T.D., A.Grossfield, and A.G. MarkelzPersistent Protein Motions in a RuggedEnergy Landscape Revealed by Normal Mode Ensemble Analysis. AcceptedJournal of Chemical Information and Modeling, 2020.

Near-Field Stationary Sample Terahertz Spectroscopic Polarimetry for Biomolecular Structural Dynamics Determination - Deng, Y.; McKinney, J. A.; George, D. K.; Niessen, K. A.; Sharma, A.; Markelz, A.G. (ACS Photonics, 2021)
THz polarimetry on environmentally sensitive and microscopic samples can provide unique insight into underlying mechanisms of complex phenomena. For example, near-field THz anisotropic absorption successfully isolated protein structural vibrations which are connected to biological function. However, to determine how these vibrations impact function requires high throughput measurements of these complex systems, which is challenged by the need for near field detection, sample environmental control and full polarization variation. Stationary sample anisotropic terahertz spectroscopy (SSATS) and near-field stationary sample anisotropic terahertz microscopy (SSATM) have been proposed using synchronous control of THz and electro optic probe polarizations along an iso-response curve. Here we realize these techniques through robust control and calibration of the THz and NIR polarization states. Both methods rapidly measure the linear dichroism in the far field and near field. Validation measurements using standard birefringent sucrose single crystals found the crystal orientation can be determined by scanning the reference polarization and the synchronous pump–probe polarization settings can be optimized to eliminate artifacts. SSATM is then used to determine spectral reproducibility and dehydration effects for a series of chicken egg white lysozyme samples. Reproducible anisotropic absorbance bands are found at about 30, 44, 55, and 62 cm–1. These bands initially sharpen with slow dehydration, similar to the increase in resolution achieved in X-ray crystallographic protein structure determination. The SSATM technique confirms the reliability of anisotropic absorption characterization of protein intramolecular vibrations and opens an avenue for rapid determination of how these long-range dynamics affect biological function.

Phonon Kinetics of Fructose at the Melting Transition - A. Davie; F. Vandrevala; S. Dampf; Y. Deng; D. K. George; E. D. Sylvester; T. Korter; E. Einarsson; J. B. Benedict; A. G. Markelz (J. Phys. Chem. C, 2021)
Terahertz time domain spectroscopy (THz TDS) is used to measure the melting kinetics of fructose molecular crystals. Combining single-crystal anisotropy measurements with density functional calculations, we assign the phonon frequencies and interrogate how specific phonons behave with melting. While nearly all the low-frequency phonons continuously red-shift with heating and melting, the lowest-energy phonon polarized along the c-axis blue-shifts at the melting temperature, suggesting an initial structural change immediately before melting. We find that the kinetics follow a 3D growth model with large activation energies, consistent with previous differential scanning calorimetry (DSC) measurements. The large activation energies indicate that multiple H-bonds must break collectively for the transition. The results suggest the generality of the kinetics for molecular crystals and that THz TDS with picosecond resolution could be used to measure ultrafast kinetics.

Evidence of Intramolecular Structural Stabilization in Light Activated State of Orange Carotenoid Protein - McKinney, J. A.; Sharma, A.; Crossen, K.; Deng, Y.; George, D. K.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. G. (Biophysical Journal, 2020)
Orange carotenoid protein (OCP) controls efficiency of the light harvesting antenna, the phycobilisome (PBS), in diverse cyanobacteria and prevents oxidative damage. It is the only known photoactive protein that uses a carotenoid, canthaxanthin, as its chromophore. The structure of OCP consists of two globular domains, connected by an unstructured loop, that forms a hydrophobic pocket for the carotenoid. In low light, canthaxanthin bound OCP is inactive and appears orange. Illumination by strong light results in an active state that interacts with the PBS to induce fluorescence quenching, a red appearance and conformational changes that include a 12Å shift by canthaxanthin into the N-terminal domain. Terahertz (THz) dynamical transition measurements and anisotropic terahertz microscopy are used to measure the intramolecular structural dynamics in the inactive and active states, which can be induced by photoexcitation or chaotropic salts. The measurements indicate that the active state has a decrease in structural flexibility, which may be related to enhanced interactions with the PBS.
ISI Document Delivery No.: KK8YX Times Cited: 0 Cited Reference Count: 0 McKinney, Jeffrey A. Sharma, Akansha Crossen, Kimberly Deng, Yanting George, Deepu K. Lechno-Yossef, Sigal Kerfeld, Cheryl Markelz, Andrea G. 64th Annual Meeting of the Biophysical-Society Feb 15-19, 2020 San Diego, CA Biophys Soc NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NIH STTRUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USA [R41 GM125486] This work is supported by NSF grants DBI 1556359 and MCB 1616529, DOE grant DE-SC0016317 and NIH STTR R41 GM125486. 1 2 Cell press Cambridge 1542-0086
Keywords: Biophysics

Long Range Correlated Motions of TIM and their Possible Influence on Enzyme Function - McKinney, J. A.; Deng, Y. T.; George, D. K.; Richard, J.; Markelz, A. G. (Biophysical Journal, 2020)
The alpha-beta barrel structure of triosephosphate isomerase (TIM) is possibly the most common among enzymes. In the case of TIM, structural dynamics are known to be essential to function. In particular the stabilization of the binding pocket by a phosphodianion “handle” of the substrate and the closing of catalytic site loops 6 and 7 over the substrate. Loop 6 moves by as much as 7 Angstroms with binding. Recently a mutant survey for human TIM (hsTIM) found kcat can change significantly for a single mutation distant from the catalytic site. Crystallographic measurements find no structural change with the mutation, suggesting a dynamical mechanism for the allosteric effect. Here we use Stationary Sample Anisotropic Terahertz Microscopy (SSATM) to measure the long-range intramolecular vibrations and determine if specific vibrations couple the allosteric and catalytic sites. SSATM isolated protein long-range structural vibrations based on the dominant displacement direction [1-4]. We examine if specific vibrational bands are associate with loop 6 and loop 7 flexibility.
ISI Document Delivery No.: KK8YX Times Cited: 0 Cited Reference Count: 4 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Niessen K.A. M.Y., 2017, BIOPHYS J, DOI [10.1016/j.bpj.2016.12.049.3., DOI 10.1016/J.BPJ.2016.12.049.3] Niessen K, 2019, OPT EXPRESS, V27, P28036, DOI 10.1364/OE.27.028036 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 McKinney, Jeffrey A. Deng, Yanting George, Deepu K. Richard, John Markelz, Andrea G. 64th Annual Meeting of the Biophysical-Society Feb 15-19, 2020 San Diego, CA Biophys Soc NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NIH STTRUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USA [R41 GM125486.1] This work is supported by NSF grants DBI 1556359 and MCB 1616529, DOE grant DE-SC0016317 and NIH STTR R41 GM125486.1. 1 Cell press Cambridge 1542-0086
Keywords: Biophysics

Stabilization of Terahertz Vibrational Modes in Illuminated Orange Carotenoid Protein Crystals - McKinney, J.; Sharma, A.; Deng, Y.; George, D.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. (2020 45th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 2020)
Orange carotenoid protein (OCP) controls efficiency of the phycobilisome (PBS), the light harvesting antenna in cyanobacteria, to prevent oxidative damage. The OCP switches from resting state to photo protective state with intense blue light illumination. Questions persist as to why OCPR interaction increases with the PBS over that with the OCPO. Here we examine the role of long-range intramolecular vibrations within OCP. Using Stationary Sample Anisotropic Terahertz Microscopy (SSATM) we measure changes in the intramolecular vibrations with photo switching. We report the first observation of switching in the intramolecular vibrations with photoexcitation. Results suggest that there is a stiffening of the molecule in the photo protective state. This increase in structural stability may enhance the interaction with the PBS change in OCP interaction with PBS. In low light, carotenoid bound OCP appears orange (OCP o ) and is inactive. Illumination by strong light converts OCP to the active, red (OCPR) state, which interacts with the PBS. A comparison of anisotropic THz microscopy measurements of dark adapted (OCP o ) and illuminated OCP crystals indicate differences in their vibrational modes that may be important for OCP-PBS interactions.

Angular Distortion Removal of THz Anisotropic Dichroism Microscope - Y. Deng; K. Niessen; A. Markelz (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
We have developed a stationary sample THz anisotropic dichroism microscope as a powerful tool for material characterization. The key innovation is the use of an iso-response curve defined by the terahertz and detection light polarizations. Here we show that following a continuous iso-response curve introduces angular distortion in the spectrum, and this distortion can be eliminated by using a discontinuous iso-response angle pairs avoiding large gradient regions. Employing this additional constraint on the relative polarizations provides a convenient technique for rapid anisotropic terahertz spectroscopy.
Keywords: absorption; angular distortion removal; Biomedical measurement; continuous iso-response curve; detection light polarizations; discontinuous iso-response angle pairs; Distortion; light polarisation; material characterization; Microscopy; proteins; rapid anisotropic terahertz spectroscopy; relative polarizations; spectroscopy; stationary sample; terahertz spectroscopy; terahertz wave spectra; THz anisotropic dichroism microscope; vibrations

Anisotropic Terahertz Microscopy of Protein Collective Vibrations: Crystal Symmetry and Hydration Dependence - McKinney, J.; Deng, Y. T.; Sharma, A.; George, D. K.; Markelz, A. G. (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
A stationary sample anisotropic terahertz microscopy technique is used to characterize the intramolecular vibrations for lysozyme. Tetragonal and triclinic crystals are compared. We find excellent reproducibility within a single crystal symmetry group. Several resonant bands are present for both symmetry groups, indicating they originate with the intramolecular vibrations and not crystal lattice phonons. Bands become more pronounced and higher frequency resonant bands begin to emerge with slight dehydration.
ISI Document Delivery No.: BQ4OX Times Cited: 0 Cited Reference Count: 4 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Legrand L, 2002, ACTA CRYSTALLOGR D, V58, P1564, DOI 10.1107/S0907444902014403 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 McKinney, Jeffrey Deng, Yanting Sharma, Akansha George, D. K. Markelz, A. G. Irmmw-thz Proceedings Paper 44th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 01-06, 2019 Paris, FRANCE Lytid, TYDEX, Swiss Terahertz, Fondat Maison Chimie, CNRS, Lab Physique ENS, Li2S, LUNA, MenloSystems, ENS, PSL Univ Paris, FYLA, ADVANTEST, Springer Nature, Soc Francaise Physique, Sorbonne Univ, Int Soc Infrared Millimeter & Terahertz Waves, IEEE, GDR NANO THz MIR NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NIHUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USA [STTR R41 GM125486] This work is supported by NSF grants DBI 1556359 and MCB 1616529, DOE grant DE-SC0016317 and NIH STTR R41 GM125486. 345 e 47th st, new york, ny 10017 usa 2162-2027

Blue Shift of a Molecular Crystal Phonon at the Solid to Liquid Phase Transition - Davie, Alex; Vandrevala, Farah; Deng, Yanting; George, D.; Sylvester, Eric D.; Korter, T.; Einarsson, E.; Benedict, Jason B.; Markelz, Andrea (Bulletin of the American Physical Society, 2019)

Deuteration and Inhibitor Binding Dependence of Protein Collective Vibrations - Deng, Y. T.; McKinney, J.; Markelz, A. (Biophysical Journal, 2019)
ISI Document Delivery No.: HO2XG Times Cited: 0 Cited Reference Count: 2 Cited References: Mahajan S, 2015, ARCH BIOCHEM BIOPHYS, V567, P59, DOI 10.1016/j.abb.2014.12.020 Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 Deng, Yanting Mckinney, Jeffrey Markelz, Andrea 63rd Annual Meeting of the Biophysical-Society Mar 02-06, 2019 Baltimore, MD Biophys Soc 8 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

The Effect of Crystal Contact Forces on the Protein Global Motions - McKinney, J. A.; Deng, Y. T.; George, D.; Markelz, A. (Biophysical Journal, 2019)
ISI Document Delivery No.: HO2XG Times Cited: 0 Cited Reference Count: 1 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 McKinney, Jeffrey A. Deng, Yanting George, Deepu Markelz, Andrea 63rd Annual Meeting of the Biophysical-Society Mar 02-06, 2019 Baltimore, MD Biophys Soc 8 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

Near-field THz micropolarimetry - Niessen, K.; Deng, Y. T.; Markelz, A. G. (Optics Express, 2019)
We introduce a method for rapid determination of anisotropic terahertz absorption with sub micron resolution and high spectral integrity in the terahertz range. The method is ideal for microscopic and environmentally sensitive materials such as 2-D materials and protein crystals where the anisotropic absorption is critical to understanding underlying physics. We introduce the idea of using an iso-response relationship between the THz polarization and electro optic probe polarization to enable stationary sample polarization measurements covering a full 2 pi polarization dependence measurement. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
ISI Document Delivery No.: JB0XT Times Cited: 1 Cited Reference Count: 31 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Antoniou D, 2011, J PHYS CHEM B, V115, P15147, DOI 10.1021/jp207876k Bagsican FR, 2017, SCI REP-UK, V7, DOI 10.1038/s41598-017-01883-1 Baxter JB, 2006, J PHYS CHEM B, V110, P25229, DOI 10.1021/jp064399a BROOKS B, 1985, P NATL ACAD SCI USA, V82, P4995, DOI 10.1073/pnas.82.15.4995 Chen JY, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2748852 Chhowalla M, 2013, NAT CHEM, V5, P263, DOI [10.1038/NCHEM.1589, 10.1038/nchem.1589] Cote Y, 2017, BIOPHYS J, V112, P2575, DOI 10.1016/j.bpj.2017.05.018 Dhillon SS, 2017, J PHYS D APPL PHYS, V50, DOI 10.1088/1361-6463/50/4/043001 Docherty CJ, 2014, ACS NANO, V8, P11147, DOI 10.1021/nn5034746 Ebbinghaus S, 2007, P NATL ACAD SCI USA, V104, P20749, DOI 10.1073/pnas.0709207104 Fan ST, 2014, J PHYS D APPL PHYS, V47, DOI 10.1088/0022-3727/47/37/374009 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Hayes D, 2011, FARADAY DISCUSS, V150, P459, DOI 10.1039/c0fd00030b Hirota Y, 2006, OPT EXPRESS, V14, P4486, DOI 10.1364/OE.14.004486 Huang B, 2017, NATURE, V546, P270, DOI 10.1038/nature22391 Jin WC, 2018, NAT COMMUN, V9, DOI 10.1038/s41467-018-07547-6 Lang D, 2018, REV SCI INSTRUM, V89, DOI 10.1063/1.5016281 Markelz A, 2002, PHYS MED BIOL, V47, P3797, DOI 10.1088/0031-9155/47/21/318 Meireles L, 2011, PROTEIN SCI, V20, P1645, DOI 10.1002/pro.711 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 Ostroverkhova O, 2006, APPL PHYS LETT, V89, DOI 10.1063/1.2387135 Planken PCM, 2011, J INFRARED MILLIM TE, V32, P975, DOI 10.1007/s10762-011-9824-3 Planken PCM, 2001, J OPT SOC AM B, V18, P313, DOI 10.1364/JOSAB.18.000313 Serita K, 2019, PHOTONICS-BASEL, V6, DOI 10.3390/photonics6010012 Vinh NQ, 2011, J AM CHEM SOC, V133, P8942, DOI 10.1021/ja200566u You JW, 2018, NANO CONVERG, V5, DOI 10.1186/s40580-018-0158-x Zhao C, 2017, NAT NANOTECHNOL, V12, P757, DOI [10.1038/NNANO.2017.68, 10.1038/nnano.2017.68] Niessen, Katherine Deng, Yanting Markelz, A. G. National Science FoundationNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; U.S. Department of EnergyUnited States Department of Energy (DOE) [DE-SCO016317]; National Institute of General Medical SciencesUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [STTR R41 GM125486] National Science Foundation (DBI 1556359, MCB 1616529); U.S. Department of Energy DE-SCO016317); National Institute of General Medical Sciences (STTR R41 GM125486). 1 3 9 Optical soc amer Washington
Keywords: binding; conductivity; dynamics; modes; Optics; polarization modulation; Terahertz; time-domain spectroscopy; wse2

Protein Intramolecular Motions with Deuteration and Inhibitor Binding Dependence - Deng, Y.; McKinney, J.; Romo, T.; Grossfield, A.; Markelz, A. G. (APS R63.003, 2019)

Spectral Assignment of Lysozyme Collective Vibrations - Deng, Y. T.; McKinney, J.; Romo, T.; Grossfield, A.; Markelz, A. (Biophysical Journal, 2019)
Global structural vibrations at terahertz (THz) frequencies have been associated with protein function and allosteric control. A chief obstacle to utilizing this control mechanism has been measurement of specific motions. Recently it was shown that while the vibrational density of states, and isotropic absorption spectra are broad and featureless, collective vibrations can be isolated based on their directionality using aligned samples (realized with protein crystals) and anisotropic THz microscopy [1]. However the assignment of resonant bands to specific structural motions was complicated by the high symmetry of the tetragonal crystals used, and the slow experimental method. To structurally map the vibrations of the chicken egg white lysozyme (CEWL) we measure anisotropic absorption of triclinic crystals using our new technique: ideal polarization varying anisotropic THz microscopy (IPV-ATM). The low symmetry triclinic crystals provide absolute protein orientation, and the near field IPV-ATM rapidly measures broadband terahertz linear dichroism of the microcrystals. All measurements were performed at room temperature under 100% humidity conditions. The unit cell parameters of triclinic lysozyme nitrate crystals, α = 28.5A°, b = 32.7A°, c = 35.1A°, α = 88.2°, β = 108.9°, γ = 111.9°, belonging to the P1 space group, were determined by X-ray diffraction before and after THz measurements. The intramolecular vibrational absorbance of the triclinic crystals has a more complex polarization dependence than the higher symmetry tetragonal crystals, as expected. While the tetragonal crystals have two strong bands at 45cm−1 and 55cm−1, the triclinic crystals have a series of narrow bands between 40 and 60cm−1 and a prominent band at 30cm−1. We compare the measured spectra to normal mode ensemble averaged calculations to assign the observed resonances, and isolating which collective motions impact the catalytic site.
ISI Document Delivery No.: HO2XG Times Cited: 0 Cited Reference Count: 1 Cited References: Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 Deng, Yanting Mckinney, Jeffrey Romo, Tod Grossfield, Alan Markelz, Andrea 63rd Annual Meeting of the Biophysical-Society Mar 02-06, 2019 Baltimore, MD Biophys Soc 8 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

Increase in Dynamical Collectivity and Directionality of Orange Carotenoid Protein in the Photo-Protective State - Deng, Y. T.; Luck, C. H.; Romo, T. D.; Grossfield, A. M.; Bandara, S.; Ren, Z.; Yang, X. J.; Markelz, A. G. (Biophysical Journal, 2018)
ISI Document Delivery No.: GD5RB Times Cited: 1 Cited Reference Count: 0 Deng, Yanting Luck, Catherine H. Romo, Tod D. Grossfield, Alan M. Bandara, Sepalika Ren, Zhong Yang, Xiaojing Markelz, Andrea G. 62nd Annual Meeting of the Biophysical-Society Feb 17-21, 2018 San Francisco, CA Biophys Soc 1 7 Cell press Cambridge 1542-0086
Keywords: Biophysics

Measuring Protein Intramolecular Dynamics with Terahertz Light: Functional Changes and Relevance to Biology - Xu, M.; Deng, Y.; Luck, C.; Sharma, A.; Markelz, A. (APS 2018, 2018)

Rapid Terahertz Dichroism Near Field Microscopy for Biomolecular Intramolecular Vibrational Spectroscopy - Deng, Y.; Niessen, K.; Markelz, A. (APS 2018, 2018)

Terahertz Light Fingerprints Biomolecular Dynamics - Deng, Yanting; Xu, Mengyang; Niessen, Katherine A; George, Deepu Koshy; Markelz, Andrea G (CLEO: Science and Innovations, 2018)

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
ISI Document Delivery No.: EI0HL Times Cited: 541 Cited Reference Count: 209 Cited References: Adam AJL, 2011, J INFRARED MILLIM TE, V32, P976, DOI 10.1007/s10762-011-9809-2 Ahmed SS, 2012, IEEE MICROW MAG, V13, P26, DOI 10.1109/MMM.2012.2205772 Alliance N., 2015, CISC VIS NETW IND GL, P1 [Anonymous], 2013, 178512012 IEEE [Anonymous], 2014, IEEE T ELECT DEVICES, V61 [Anonymous], 2012, 178522016 IEEE [Anonymous], 2015, P17852 IEEE Appleby R, 2015, P SOC PHOTO-OPT INS, V9462 Arnone DD, 1999, PROC SPIE, V3828, P209, DOI 10.1117/12.361037 Ashworth PC, 2009, OPT EXPRESS, V17, P12444, DOI 10.1364/OE.17.012444 AUSTON DH, 1988, IEEE J QUANTUM ELECT, V24, P184, DOI 10.1109/3.114 Barbieri S, 2011, NAT PHOTONICS, V5, P306, DOI [10.1038/NPHOTON.2011.49, 10.1038/nphoton.2011.49] Barker RJ., 2005, MODERN MICROWAVE MIL Basov DN, 2011, REV MOD PHYS, V83, P471, DOI 10.1103/RevModPhys.83.471 Bauwens M. F., 2014, P IEEEMTT S INT MICR, P1, DOI [10.1109/MWSYM.2014.68486 07, DOI 10.1109/MWSYM.2014.6848607] Beard MC, 2002, NANO LETT, V2, P983, DOI 10.1021/nl0256210 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Bechtel HA, 2014, P NATL ACAD SCI USA, V111, P7191, DOI 10.1073/pnas.1400502111 Belkin MA, 2008, OPT EXPRESS, V16, P3242, DOI 10.1364/OE.16.003242 Belkin MA, 2015, PHYS SCRIPTA, V90, DOI 10.1088/0031-8949/90/11/118002 Bell R., 2012, INTRO FOURIER TRANSF Berry CW, 2013, NAT COMMUN, V4, DOI 10.1038/ncomms2638 Blanchard F, 2011, OPT EXPRESS, V19, P8277, DOI 10.1364/OE.19.008277 Blau J, 2013, P FREE EL LAS FEL 20, P486 Booske JH, 2011, IEEE T THZ SCI TECHN, V1, P54, DOI 10.1109/TTHZ.2011.2151610 Booske JH, 2008, PHYS PLASMAS, V15, DOI 10.1063/1.2838240 Boppel S, 2012, 2012 IEEE 12TH TOPICAL MEETING ON SILICON MONOLITHIC INTEGRATED CIRCUITS IN RF SYSTEMS (SIRF), P77, DOI 10.1109/SiRF.2012.6160142 Burghoff D, 2014, NAT PHOTONICS, V8, P462, DOI 10.1038/nphoton.2014.85 Busch SF, 2014, J INFRARED MILLIM TE, V35, P993, DOI 10.1007/s10762-014-0113-9 Byrne MB, 2011, APPL PHYS LETT, V98, DOI 10.1063/1.3579258 Carr GL, 2002, NATURE, V420, P153, DOI 10.1038/nature01175 Carranza IE, 2015, IEEE T THZ SCI TECHN, V5, P892, DOI 10.1109/TTHZ.2015.2463673 Castro-Camus E, 2007, OPT EXPRESS, V15, P7047, DOI 10.1364/OE.15.007047 Chan WL, 2007, REP PROG PHYS, V70, P1325, DOI 10.1088/0034-4885/70/8/R02 Chattopadhyay G, 2011, IEEE T THZ SCI TECHN, V1, P33, DOI 10.1109/TTHZ.2011.2159561 Chen HT, 2003, APPL PHYS LETT, V83, P3009, DOI 10.1063/1.1616668 Chen JN, 2012, NATURE, V487, P77, DOI 10.1038/nature11254 Cocker T L, 2016, J PHYS D, V16, P1421 Cocker TL, 2013, NAT PHOTONICS, V7, P620, DOI [10.1038/NPHOTON.2013.151, 10.1038/nphoton.2013.151] Coleman B, 2001, Issue Brief (Public Policy Inst (Am Assoc Retired Pers)), P1 Cooper KB, 2014, IEEE MICROW MAG, V15, P51, DOI 10.1109/MMM.2014.2356092 Cruz F C, 2007, C MICR OPT Cunningham J, 2010, ELECTRON LETT, V46, pS34, DOI 10.1049/el.2010.3317 Dean P, 2011, OPT LETT, V36, P2587, DOI 10.1364/OL.36.002587 Dietz RJB, 2014, OPT LETT, V39, P6482, DOI 10.1364/OL.39.006482 Dietz RJB, 2014, OPT EXPRESS, V22, P19411, DOI 10.1364/OE.22.019411 Dobrovolsky V, 2007, SEMICOND SCI TECH, V22, P103, DOI 10.1088/0268-1242/22/2/017 Ducournau G, 2014, IEEE T THZ SCI TECHN, V4, P328, DOI 10.1109/TTHZ.2014.2309006 Dunsmore J.P., 2012, HDB MICROWAVE COMPON Duvillaret L, 1999, APPL OPTICS, V38, P409, DOI 10.1364/AO.38.000409 Eisele M, 2014, NAT PHOTONICS, V8, P841, DOI [10.1038/nphoton.2014.225, 10.1038/NPHOTON.2014.225] Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fathololoumi S, 2012, OPT EXPRESS, V20, P3866, DOI 10.1364/OE.20.003866 Fausti D, 2011, SCIENCE, V331, P189, DOI 10.1126/science.1197294 Federici J, 2010, J APPL PHYS, V107, DOI 10.1063/1.3386413 Fei Z, 2012, NATURE, V487, P82, DOI 10.1038/nature11253 FETTERMAN HR, 1974, APPL PHYS LETT, V24, P70, DOI 10.1063/1.1655098 Freeman JR, 2013, OPT EXPRESS, V21, P16162, DOI 10.1364/OE.21.016162 Frisk U, 2003, ASTRON ASTROPHYS, V402, pL27, DOI 10.1051/0004-6361:20030335 Garet F, 2014, APPL PHYS LETT, V105, DOI 10.1063/1.4890732 Gavrilov NG, 2007, NUCL INSTRUM METH A, V575, P54, DOI 10.1016/j.nima.2007.01.023 Gensch M., 2013, P 35 INT FREE EL LAS, P474 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giliberti V, 2013, APPL PHYS LETT, V103, DOI 10.1063/1.4819734 Grant J, 2013, LASER PHOTONICS REV, V7, P1043, DOI 10.1002/lpor.201300087 Green B, 2016, SCI REP-UK, V6, DOI 10.1038/srep22256 Griffith P.R., 2007, FOURIER TRANSFORM IN GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Gruene P, 2008, SCIENCE, V321, P674, DOI 10.1126/science.1161166 Han NR, 2014, OPT LETT, V39, P3480, DOI 10.1364/OL.39.003480 Han RN, 2013, IEEE J SOLID-ST CIRC, V48, P2296, DOI 10.1109/JSSC.2013.2269856 Hanham SM, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4927242 Hassel J, 2015, PROC SPIE, V9651, DOI 10.1117/12.2197522 Hauri CP, 2011, APPL PHYS LETT, V99, DOI 10.1063/1.3655331 He W, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4932099 Hebling J, 2002, OPT EXPRESS, V10, P1161, DOI 10.1364/OE.10.001161 Heinz E, 2015, J INFRARED MILLIM TE, V36, P879, DOI 10.1007/s10762-015-0170-8 Henry SC, 2012, OPT ENG, V51, DOI 10.1117/1.OE.51.9.091603 Hesler J L, 2006, P 7 INT S SPAC TER T, P215 Hintzsche H, 2012, CRIT REV ENV SCI TEC, V42, P2408, DOI 10.1080/10643389.2011.574206 Hishida M, 2011, PHYS REV LETT, V106, DOI 10.1103/PhysRevLett.106.158102 Ho IC, 2010, OPT EXPRESS, V18, P2872, DOI 10.1364/OE.18.002872 HU BB, 1995, OPT LETT, V20, P1716, DOI 10.1364/OL.20.001716 Huang C, 2012, PHYS REV B, V85 Huber R, 2001, NATURE, V414, P286, DOI 10.1038/35104522 Jankowiak A., 2013, Synchrotron Radiation News, V26, P22, DOI 10.1080/08940886.2013.791212 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Jepsen PU, 2005, OPT LETT, V30, P29, DOI 10.1364/OL.30.000029 JUICE-Jupiter Icy Moons Explorer, 2014, SRE20141 JUICE EUR S, P1 Kallfass I, 2011, IEEE T THZ SCI TECHN, V1, P477, DOI 10.1109/TTHZ.2011.2160021 Kampfrath T, 2013, NAT PHOTONICS, V7, P680, DOI [10.1038/nphoton.2013.184, 10.1038/NPHOTON.2013.184] Kan T, 2015, NAT COMMUN, V6, DOI 10.1038/ncomms9422 Karpowicz N, 2008, APPL PHYS LETT, V92, DOI 10.1063/1.2828709 Kehr SC, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.256403 Kemp MC, 2011, IEEE T THZ SCI TECHN, V1, P282, DOI 10.1109/TTHZ.2011.2159647 Khalid A, 2014, J APPL PHYS, V115, DOI 10.1063/1.4868705 Kirley MP, 2015, IEEE T THZ SCI TECHN, V5, P1012, DOI 10.1109/TTHZ.2015.2468074 Kiwa T, 2003, OPT LETT, V28, P2058, DOI 10.1364/OL.28.002058 Koch M, 2001, NATO SCI SER II MATH, V27, P241 Koenig S, 2013, NAT PHOTONICS, V7, P977, DOI [10.1038/nphoton.2013.275, 10.1038/NPHOTON.2013.275] Kohler R, 2002, NATURE, V417, P156, DOI 10.1038/417156a Koppens FHL, 2014, NAT NANOTECHNOL, V9, P780, DOI [10.1038/nnano.2014.215, 10.1038/NNANO.2014.215] Kosarev A, 2010, SOLID STATE ELECTRON, V54, P417, DOI 10.1016/j.sse.2009.12.032 Kundu I, 2014, OPT EXPRESS, V22, P16595, DOI 10.1364/OE.22.016595 Kuznetsov SA, 2010, KEY ENG MATER, V437, P276, DOI 10.4028/www.scientific.net/KEM.437.276 Langevin Y, 2005, PAYLOAD MISSION DEFI LaRue JL, 2015, PHYS REV LETT, V115, DOI 10.1103/PhysRevLett.115.036103 Leitenstorfer A, 2014, NEW J PHYS, V16, DOI 10.1088/1367-2630/16/4/045016 Leitner DM, 2006, INT REV PHYS CHEM, V25, P553, DOI 10.1080/01442350600862117 Li LH, 2014, ELECTRON LETT, V50, P309, DOI 10.1049/el.2013.4035 Liu L, 2010, IEEE MICROW WIREL CO, V20, P504, DOI 10.1109/LMWC.2010.2055553 Liu SC, 2016, OPT EXPRESS, V24, P2728, DOI 10.1364/OE.24.002728 Lu X H, 2008, P SOC PHOTO-OPT INS, V7277 Luukanen A, 2003, APPL PHYS LETT, V82, P3970, DOI 10.1063/1.1579562 Mann C, 2009, P SOC PHOTO-OPT INS, V7311, P3970 Mickan S, 2004, PROC SPIE, V5277, P54, DOI 10.1117/12.530386 Mineo M, 2010, IEEE T ELECTRON DEV, V57, P3169, DOI 10.1109/TED.2010.2071876 Mittleman DM, 1996, IEEE J SEL TOP QUANT, V2, P679, DOI 10.1109/2944.571768 Mittleman DM, 1999, APPL PHYS B-LASERS O, V68, P1085, DOI 10.1007/s003400050750 Moon K, 2012, APPL PHYS LETT, V101, DOI 10.1063/1.4733475 Muller AS, 2010, REV ACCEL SCI TECH, V3, P165, DOI 10.1142/S1793626810000427 Muller R, 2015, J INFRARED MILLIM TE, V36, P654, DOI 10.1007/s10762-015-0163-7 Naftaly M, 2015, TERAHERTZ METROLOGY, P1 Nagai M, 2015, OPT EXPRESS, V23, P4641, DOI 10.1364/OE.23.004641 Nagatsuma T, 2012, OPT EXPRESS, V21, P477 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Navarro-Cia M, 2015, J INFRARED MILLIM TE, V36, P542, DOI 10.1007/s10762-015-0157-5 Nielsen K, 2009, OPT EXPRESS, V17, P8592, DOI 10.1364/OE.17.008592 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 Nordquist CD, 2011, IEEE J SEL TOP QUANT, V17, P130, DOI 10.1109/JSTQE.2010.2049095 Oh SJ, 2012, J INFRARED MILLIM TE, V33, P74, DOI 10.1007/s10762-011-9847-9 Ojefors E, 2009, IEEE J SOLID-ST CIRC, V44, P1968, DOI 10.1109/JSSC.2009.2021911 Ortolani M, 2008, PHYS REV LETT, V97 Ozerov M, 2014, PHYS REV LETT, V113, DOI 10.1103/PhysRevLett.113.157205 Paoloni C, 2013, IEEE T ELECTRON DEV, V60, P1236, DOI 10.1109/TED.2013.2240686 Parrott EPJ, 2015, APPL SPECTROSC, V69, P1, DOI 10.1366/14-07707 Patrashin M, 2015, IEEE T ELECTRON DEV, V62, P1068, DOI 10.1109/TED.2015.2393358 Peiponen K. E., 2013, TERAHERTZ SPECTROSCO, V171 Peng K, 2015, NANO LETT, V15, P206, DOI 10.1021/nl5033843 Pickwell E, 2004, APPL PHYS LETT, V84, P2190, DOI 10.1063/1.1688448 Ponnampalam L, 2011, J LIGHTWAVE TECHNOL, V29, P2229, DOI 10.1109/JLT.2011.2158186 Pupeza I, 2007, OPT EXPRESS, V15, P4335, DOI 10.1364/OE.15.004335 Rauter P, 2015, LASER PHOTONICS REV, V9, P452, DOI 10.1002/lpor.201500095 Reid CB, 2011, PHYS MED BIOL, V56, P4333, DOI 10.1088/0031-9155/56/14/008 Reid J R, 2012, IEEE 12 TOP M SIL MO, P17 Rosch M, 2015, NAT PHOTONICS, V9, P42, DOI [10.1038/nphoton.2014.279, 10.1038/NPHOTON.2014.279] Rudd JV, 2000, PROC SPIE, V3934, P27, DOI 10.1117/12.386344 Rymanov V, 2015, PHOTONICS, V2, DOI 10.3390/photonics2041152 SANTOS Daisy Conceicao, 2014, THESIS Scherger B, 2011, APPL OPTICS, V50, P2256, DOI 10.1364/AO.50.002256 Schleicher JM, 2009, J APPL PHYS, V105, DOI 10.1063/1.3133093 Schumann S, 2012, OPT EXPRESS, V20, P19200, DOI 10.1364/OE.20.019200 Seeds AJ, 2015, J LIGHTWAVE TECHNOL, V33, P579, DOI 10.1109/JLT.2014.2355137 Sell A, 2008, OPT LETT, V33, P2767, DOI 10.1364/OL.33.002767 Shams H, 2015, IEEE PHOTONICS J, V7, DOI 10.1109/JPHOT.2015.2438437 Shams H, 2014, OPT EXPRESS, V22, P23465, DOI 10.1364/OE.22.023465 Shen YC, 2004, APPL PHYS LETT, V85, P164, DOI 10.1063/1.1768313 Simoens F., 2014, PHILOS T A, V372, P1 Simoens F, 2011, 36 INT C INFR MILL T, P1 Singh A, 2015, OPT EXPRESS, V23, P6656, DOI 10.1364/OE.23.006656 Sirtori C, 2013, NAT PHOTONICS, V7, P691, DOI [10.1038/NPHOTON.2013.208, 10.1038/nphoton.2013.208] SMITH PR, 1988, IEEE J QUANTUM ELECT, V24, P255, DOI 10.1109/3.121 Son JH, 2013, NANOTECHNOLOGY, V24, DOI 10.1088/0957-4484/24/21/214001 Swinyard B, 2013, SPIE SENSORS SYSTEMS Sy S, 2010, PHYS MED BIOL, V55, P7587, DOI 10.1088/0031-9155/55/24/013 Taylor ZD, 2015, IEEE T THZ SCI TECHN, V5, P184, DOI 10.1109/TTHZ.2015.2392628 Teppati V, 2013, CAMB RF MICROW ENG, P1, DOI 10.1017/CBO9781139567626 Tewari P, 2012, P SPIE, V8261 Thomas B., 2014, P 39 INT C INFR MILL, P1 Thumm M, 2014, KIT SCI REPORTS, V7693 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Truong BCQ, 2015, IEEE T BIO-MED ENG, V62, P699, DOI 10.1109/TBME.2014.2364025 Turcinkova D, 2015, APPL PHYS LETT, V106, DOI 10.1063/1.4916653 Turner GM, 2002, J PHYS CHEM B, V106, P11716, DOI 10.1021/jp025844e van der Valk NCJ, 2002, APPL PHYS LETT, V81, P1558, DOI 10.1063/1.1503404 van Dijk F, 2014, IEEE PHOTONIC TECH L, V26, P965, DOI 10.1109/LPT.2014.2309353 Vicario C, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.213901 Vinh NQ, 2015, J CHEM PHYS, V142, DOI 10.1063/1.4918708 Vitiello MS, 2012, NAT PHOTONICS, V6, P525, DOI 10.1038/nphoton.2012.145 Vitiello MS, 2015, OPT EXPRESS, V23, P5167, DOI 10.1364/OE.23.005167 Vitiello MS, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms6884 Wade A, 2009, NAT PHOTONICS, V3, P41, DOI 10.1038/NPHOTON.2008.251 Wallace B., 2015, SPIE NEWSROOM, DOI [10.1117/2.1201503.005871, DOI 10.1117/2.1201503.005871] Wallace VP, 2004, BRIT J DERMATOL, V151, P424, DOI 10.1111/j.1365-2133.2004.06129.x Wang FH, 2015, OPTICA, V2, P944, DOI 10.1364/OPTICA.2.000944 Weightman P, 2012, PHYS BIOL, V9, DOI 10.1088/1478-3975/9/5/053001 Wienold M, 2014, OPT EXPRESS, V22, P3334, DOI 10.1364/OE.22.003334 Wilk R, 2007, C LAS EL BALT MD Williams BS, 2006, ELECTRON LETT, V42, P89, DOI 10.1049/el:20063921 Williams GP, 2006, REP PROG PHYS, V69, P301, DOI 10.1088/0034-4885/69/2/R01 Williams GP, 2008, NAT PHYS, V4, P356, DOI 10.1038/nphys958 Williams MRC, 2013, J PHYS CHEM B, V117, P10444, DOI 10.1021/jp406730a Williams R, 2013, PHYS MED BIOL, V58, P373, DOI 10.1088/0031-9155/58/2/373 Withayachumnankul W, 2008, J OPT SOC AM B, V25, P1059, DOI 10.1364/JOSAB.25.001059 Woerner M, 2013, NEW J PHYS, V15, DOI 10.1088/1367-2630/15/2/025039 Woodward RM, 2003, J INVEST DERMATOL, V120, P72, DOI 10.1046/j.1523-1747.2003.12013.x Wu X, OPT LETT, V39, P5403 Wu ZR, 2013, REV SCI INSTRUM, V84, DOI 10.1063/1.4790427 Xu J, 2003, PROC SPIE, V5268, P19, DOI 10.1117/12.518533 Yamashita M, 2011, OPT EXPRESS, V19, P10864, DOI 10.1364/OE.19.010864 Yan F, 2013, J INFRARED MILLIM TE, V34, P489, DOI 10.1007/s10762-013-0005-4 Yang SH, 2014, IEEE T THZ SCI TECHN, V4, P575, DOI 10.1109/TTHZ.2014.2342505 Yeh KL, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2734374 Zamora A, 2015, IEEE MTT S INT MICR Zhao JF, 2011, IEEE T ELECTRON DEV, V58, P1221, DOI 10.1109/TED.2011.2109723 Zheludev NI, 2012, NAT MATER, V11, P917, DOI [10.1038/NMAT3431, 10.1038/nmat3431] Zhou Y, 2010, PROG ELECTROMAGN RES, V105, P71, DOI 10.2528/PIER10041806 Zibik EA, 2009, NAT MATER, V8, P803, DOI [10.1038/nmat2511, 10.1038/NMAT2511] Dhillon, S. S. Vitiello, M. S. Linfield, E. H. Davies, A. G. Hoffmann, Matthias C. Booske, John Paoloni, Claudio Gensch, M. Weightman, P. Williams, G. P. Castro-Camus, E. Cumming, D. R. S. Simoens, F. Escorcia-Carranza, I. Grant, J. Lucyszyn, Stepan Kuwata-Gonokami, Makoto Konishi, Kuniaki Koch, Martin Schmuttenmaer, Charles A. Cocker, Tyler L. Huber, Rupert Markelz, A. G. Taylor, Z. D. Wallace, Vincent P. Zeitler, J. Axel Sibik, Juraj Korter, Timothy M. Ellison, B. Rea, S. Goldsmith, P. Cooper, Ken B. Appleby, Roger Pardo, D. Huggard, P. G. Krozer, V. Shams, Haymen Fice, Martyn Renaud, Cyril Seeds, Alwyn Stoehr, Andreas Naftaly, Mira Ridler, Nick Clarke, Roland Cunningham, John E. Johnston, Michael B. Huggard, Peter/U-2150-2019; Konishi, Kuniaki/AAN-3624-2020; Zeitler, J. Axel/B-4885-2008; Paoloni, Claudio/AAH-9824-2019; Hoffmann, Matthias C./N-1082-2019; Wallace, Vincent P/A-9320-2012; Johnston, Michael/B-9813-2008; Castro-Camus, Enrique/V-6861-2019; Krozer, Viktor/P-5623-2014; Hoffmann, Matthias C/B-3893-2009; PAOLONI, CLAUDIO/AAA-3211-2020; Gonokami, Makoto/F-3641-2012; Shams, Haymen/H-3754-2012; Ridler, Nick/AAN-9637-2020; Huber, Rupert/N-4126-2018 Konishi, Kuniaki/0000-0003-2389-9787; Zeitler, J. Axel/0000-0002-4958-0582; Hoffmann, Matthias C./0000-0002-3596-9853; Wallace, Vincent P/0000-0003-3814-5400; Johnston, Michael/0000-0002-0301-8033; Krozer, Viktor/0000-0002-2387-1947; Hoffmann, Matthias C/0000-0002-3596-9853; PAOLONI, CLAUDIO/0000-0002-0265-0862; Shams, Haymen/0000-0002-5333-6478; Huber, Rupert/0000-0001-6617-9283; Davies, Alexander/0000-0002-1987-4846; Seeds, Alwyn/0000-0002-5228-627X; Castro-Camus, Enrique/0000-0002-8218-9155; Cunningham, John/0000-0002-1805-9743; Naftaly, Mira/0000-0002-0671-822X; Cumming, David/0000-0002-7838-8362 Engineering and Physical Sciences Research CouncilUK Research & Innovation (UKRI)Engineering & Physical Sciences Research Council (EPSRC) [EP/P015883/1, EP/M00306X/1, EP/K023349/1, EP/M017095/1, EP/L026597/1, EP/J017671/1] Funding Source: researchfish; Natural Environment Research CouncilUK Research & Innovation (UKRI)NERC Natural Environment Research Council [NER/Z/S/2003/00642, NE/L012375/1, NER/Z/S/2000/01292] Funding Source: researchfish; Science and Technology Facilities CouncilUK Research & Innovation (UKRI)Science & Technology Facilities Council (STFC) [ST/P002056/1] Funding Source: researchfish; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Molecular and Cellular BioscienceNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1616529] Funding Source: National Science Foundation 566 30 462 Iop publishing ltd Bristol 1361-6463
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Escaping the Water Cage: Protein Intramolecular Vibrations and the Dynamical Transition - Xu, M. Y.; Niessen, K. A.; Deng, Y. T.; Michki, N. S.; Markelz, A. G. (Biophysical Journal, 2017)
ISI Document Delivery No.: EW3DR Times Cited: 0 Cited Reference Count: 0 Xu, Mengyang Niessen, Katherine A. Deng, Yanting Michki, Nigel S. Markelz, Andrea G. 58th Annual Meeting of the Biophysical-Society Feb 15-19, 2014 San Francisco, CA Biophys Soc NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317] This work was supported by NSF (DBI 1556359 and MCB 1616529), and DOE DE-SC0016317. 7 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

Global Picosecond Structural Dynamics of Orange Carotenoid Protein in Photo/Chemical Activated Signaling States - Deng, Y.; Xu, M.; Liu, H.; Blankenship, R.; Markelz, A. (APS 2017 S4.002, 2017)

Importance of Protein Vibration Directionality on Function - Niessen, Katherine A.; Xu, Mengyang; Deng, Yanting; Snell, Edward H.; Markelz, Andrea G. (Biophysical Journal, 2017)
Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 1 58th Annual Meeting of the Biophysical-Society Feb 15-19, 2014 San Francisco, CA Biophys Soc

Orange Carotenoid Protein Picosecond Dynamics Changes with Photo and Chemical Activation - Deng, Y. T.; Xu, M. Y.; Liu, H. J.; Blankenship, R. E.; Markelz, A. G. (Biophysical Journal, 2017)
ISI Document Delivery No.: EW3DS Times Cited: 0 Cited Reference Count: 3 Cited References: King JD, 2014, FEBS LETT, V588, P4561, DOI 10.1016/j.febslet.2014.10.024 Wilson A, 2006, PLANT CELL, V18, P992, DOI 10.1105/tpc.105.040121 Wilson A, 2008, P NATL ACAD SCI USA, V105, P12075, DOI 10.1073/pnas.0804636105 Deng, Yanting Xu, Mengyang Liu, Haijun Blankenship, Robert E. Markelz, Andrea G. 58th Annual Meeting of the Biophysical-Society Feb 15-19, 2014 San Francisco, CA Biophys Soc Liu, Haijun/0000-0003-0537-0302 14 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

Anisotropic Absorption Measurements Reveal Protein Dynamical Transition in Intramolecular Vibrations - Xu, M. Y.; Niessen, K.; Michki, N.; Deng, Y. T.; Snell, E.; Markelz, A. G. (2016 41st International Conference on Infrared, Millimeter, and Terahertz Waves, 2016)
Modeling has predicted that intramolecular structural vibrations enables proteins to access functionally important structural change. We show that the vibrational density of states and the isotropic absorption in the terahertz range are only weakly dependent on the protein functional state for several bench marking proteins. At the same time the direction of motions changes dramatically with functional state and with a resulting impact on the anisotropic absorption. Our anisotropic THz microscopy (ATM) measurements confirm this sensitivity. Here we apply the technique to the question of whether the protein dynamical transition (DT) is important to protein function. We find a strong anisotropic resonance at 70 cm(-1) rapidly increases in strength at temperatures above the DT. As these intramolecular vibrations enable protein structure to change conformation, the results suggest function will cease below DT for those proteins that require large scale conformational change.
ISI Document Delivery No.: BG7KC Times Cited: 0 Cited Reference Count: 4 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Niessen K., 2015, BIOPHYSICAL REV PETHIG R, 1995, PROTEIN SOLVENT INTE, P265 RUPLEY JA, 1991, ADV PROTEIN CHEM, V41, P37 Xu, Mengyang Niessen, Katherine Michki, Nigel Deng, Yanting Snell, Edward Markelz, A. G. Irmmw-thz Proceedings Paper 41st International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 25-30, 2016 Copenhagen, DENMARK DTU, IEEE, QMC Instruments, Danish Ctr Laser Infrastructure, DTU Fotonik, Dept Photon Engn, ARL, Carl Sberg Fdn, AF Off Sci Res, Tech Univ Denmark, IEEE Microwave Theory & Tech Soc, Azpect Photon, Ekspla, Hubner HF Syst Engn, I2S, Laser Quantum, Menlo Syst, Neaspec, Springer, TeraView, Virginia Diodes Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 345 e 47th st, new york, ny 10017 usa 2162-2027

Direct Measurements of the Long-Range Collective Vibrations of Photoactive Yellow Protein - Deng, Yanting; Xu, Mengyang; Niessen, Katherine A.; Schmidt, Marius; Markelz, Andrea G. (30th Anniversary Symposium of The Protein Society, 2016)
Long-range collective vibrations are thought to be crucial to protein functions. In the case of photoactive protein family, modeling suggests the intramolecular vibrations provide an efficient means of energy relaxation[1], feedback for enhancement of chromophore vibrations that promote structural transitions[2] and can assist in charge energy transfer[3]. As a paradigm of this family, photoactive yellow protein (PYP) is a cytoplasmic photocycling protein related to negative phototactic response to blue light in purple photosynthetic bacteria. PYP has a p-coumaric acid chromophore binding to the cysteine residue via a thioester bond, whose vibrations were found to overlap calculated vibrations of the protein scaffold. Using our unique technique of anisotropic terahertz microscopy(ATM)[4], we measure the intramolecular vibrations for PYP for the first time, including cycling between ground and blue shift (pB) states. Room temperature ATM measurements are performed in the dark and with continuous wave illumination at 488nm, resulting in a steady pB state with approximately 5% population conversion. In pB state, we find an overall decrease in the strength of resonant band in frequency range of 30-60 cm-1. Our calculated spectra using quasi-harmonic analysis indicate that our measurements are dominated by the protein vibrations, rather than the pCA chromophore, allowing us to characterize how the scaffold dynamics changes with functional states and mutations. 1. Levantino, M., et al. Nat Commun, 2015. 6. 2. Mataga, N., et al. Chem. Phys. Lett., 2002. 352(3-4): p. 220-225. 3. Fokas, A.S., et al. Photosynth. Res., 2014. 122

The Role of Dynamical Transition in Protein Function: Coupling of Protein Collective Vibrations and Water Dynamics - Xu, Mengyang; Niessen, Katherine; Deng, Yanting; Michki, Nigel; Snell, Edward; Markelz, Andrea (30th Anniversary Symposium of The Protein Society, 2016)
Computational simulations have revealed protein collective vibrations prompt structural rearrangements to accomplish biological function. However, the biological importance of collective vibrations has not been experimentally demonstrated. The attempts have been hampered by the inability to distinguish localized water or side-chain relaxational motions from protein long-range vibrations using conventional techniques. The dynamical transition (DT), extensively observed using X-ray, neutron scattering, NMR and terahertz techniques [1,2], describes a rapid increase in the temperature-dependent dynamics of critically hydrated proteins above ∼220 K, and has been attributed to thermally activated solvent motions. While some proteins lose function below the specific temperature, others do not. We suggest the difference arises from the nature of the required motions for function. Specifically, functional motions enabled by long-range vibrations will be vulnerable to DT, which require surrounding solvent to be sufficiently mobile. We explored the coupling of protein vibrations to solvent dynamics by applying a recently developed technique, anisotropy terahertz microscopy [3], to directly measure the collective vibrations for lysozyme and investigate the temperature dependence in 150-300 K range. We find long-range intramolecular vibrations occur at 220K and rapidly increase in strength with increasing temperature, consistent with enhanced access above the DT. The results suggest collective vibrations are slaved to DT, and those proteins with function reliant on these motions will cease function below DT. 1. Doster,W., et al. Phys.Rev.Lett., 2010.104(9):098101. 2. Niessen,K., et al. Biophys.Rev., 2015.7,201. 3. Acbas,G., et al. Nat.Commun., 2014.5,3076.